Conversion to the Good News - Luke 13: Hoán cải theo Tin Mừng Luca - Nguyễn, Ngọc Triều (Khoa Học Công Giáo và Đời Sống, 2022)
In the passage from Luke's Gospel, chapter 13, verses 1-5, Jesus twice affirms: "If you do not convert, you will all die in the same way". Jesus wanted the Jews to change their minds and live a converted spirit so that they would not enter the way of death. So, to better understand His teaching, we need to understand what conversion is and why He wants us to convert.